دراسة الخواص المنشئية وتصنيف الترب الجبلية الضعيفة التطور (Ochrepts) في منطقة القدموس - رقيه عادل شريف (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى تحديد خواص الترب الجبلية الضعيفة التطور (Ochrepts) في منطقة القدموس. من أجل ذلك تمت دراسة أربعة قطاعات تحت غطاء نباتي طبيعي، وقد بينت النتائج أن الترب ذات لون بني داكن في الآفاق السطحية، يتحول إلى بني محمر في الأفق (Bm). كما تميزت بارتفاع محتوى الطين في كامل القطاع، وخاصة في الأفق (Bm)، وكذلك بارتفاع محتوى الدبال في الأفق السطحي، وسيطرة الـ Ca، وMg على معقد الادمصاص، وبوجود الأفق المتحول B cambic . من الناحية التصنيفية يتبع لها خمس مجموعات عظمى؛ هي: النموذجية، والكلسية، والضحلة، والمتشققة، والرسوبية، أما من الناحية التطورية فهي تمثل حالة انتقالية مابين ترب الموليسول، وترب الغابات المشبعة بالقواعد Alfisol. وهي ترب عميقة عموماً تحت الغطاء النباتي الطبيعي، وفي التضاريس المستوية، أو قليلة الميل على مختلف مواد الأصل المنتشرة في المنطقة. The objective of this research was to determine properties of weakly developed Mountainous soils (Ochrepts) in al kadmous region. Four profiles under natural plant cover were studied, the main achieved results were: soils color was dark brown in the surface horizons, and it changed to brown reddish in Bm Horizon. Soil clay content was very high in the whole profile especially in Bm horizon, and also humus content in horizon A, calcium and magnesium were also dominants on exchange complex, and the presence of metamorphic B Cambic horizon was recorded. From a classification point of view, five main groups were recorded: Calcareous, Lithic, Vertic, Typical, Flouvents. Whereas from development point view, they represent transitionary state between Mollisol and forest soils saturated with alkali (Alfisol). The soil was generally deep under natural plant cover and plane topographic or gently sloped on different parent materials which are spread in the region.